Sinergi Pengajian Rutin dan Pengajaran TPA di PRM Jayengan: Upaya Membangun Masyarakat Madani Berlandaskan Al-Qur'an: Regular Religious Gathering and TPA Teaching Synergy at PRM Jayengan: An Effort to Build a Civil Society Based on the Qur’an - Ahmad Nurrohim; Adnan Faisal Syaifudin; Aditya Candra Arifudin; Luthfi Abdul Ghoni; Gifari Firdaus Fathan; Joky Awan; Naufal Fadila Azhar (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
This article discusses the implementation of Field Work Practice and Community Service (PKL-P) held at the Muhammadiyah Branch Leadership (PRM) Jayengan. The purpose of this program is to achieve two main things: first, to provide students with the opportunity to gain real experience in implementing Muhammadiyah values in society; second, to actively contribute to strengthening and empowering the PRM Jayengan community through programs that are in accordance with local needs. The implementation of PKL-P uses a qualitative approach by conducting direct observations, in-depth interviews with community leaders and PRM members, and collecting documents related to activities. The focus of this service is the renewal of religious studies and improving the quality of Al-Qur'an education at the Al-Qur'an Education Park (TPA). The results of this activity show that PKL-P students are able to identify challenges and potentials in PRM Jayengan, and have succeeded in implementing various community service programs that have a positive impact, such as increasing congregation participation in routine religious studies and optimizing TPA activities. In addition, this program has also succeeded in increasing collective awareness of the importance of PRM's role in fostering society. In conclusion, the Muhammadiyah internship program at PRM Jayengan not only provides valuable experience for students, but also provides direct contribution to strengthening the preaching and empowerment of the Muhammadiyah community.